Necrotizing Soft Tissue Infections: Surgeon's Prospective - Shashi Prakash Mishra; Shivanshu Singh; Sanjeev Kumar Gupta (Hindawi Limited, 2013)
Necrotizing soft tissue infections (NSTIs) are fulminant infections of any layer of the soft tissue compartment associated with widespread necrosis and systemic toxicity. Delay in diagnosing and treating these infections increases the risk of mortality. Early and aggressive surgical debridement with support for the failing organs significantly improves the survival. Although there are different forms of NSTIs like Fournier's gangrene or clostridial myonecrosis, the most important fact is that they share common pathophysiology and principles of treatment. The current paper summarizes the pathophysiology, clinical features, the diagnostic workup required and the treatment principles to manage these cases.